Український патріот, думський депутат і російський «земгусар» Микола Біляшівський у 1906-1917 рр. - Коник, О.О. (Історичний архів. Наукові студії, 2015)
Розглянуто особистість українського вченого, археолога і музейного діяча Миколи Біляшевського як учасника важливих політичних процесів у Російській імперії на початку ХХ ст., одночасно у кількох іпостасях: українського патріота, кадета, думського депутата і російського земського діяча. Висвітлено казус із різночитаннями прізвища та по батькові депутата Біля шевського. Зроблено спробу проаналізувати мотиви його діяльності в цей період, впливи близького оточення на політичну позицію і прийняття рішень, особливості життєвої стратегії в цілому. На основі архівних документів висвітлено конкретні обставини його роботи як представника Всеросійського союзу міст у зайнятій російськими військами Галичині та Буковині в роки Першої світової війни.
Відзначено, що високий рівень спеціальних знань та професіоналізм Біляшевського разом з обережним ставленням до радикальних політичних рішень дозволили йому уникнути репресій від урядів, що часто змінювалися в Києві в ході революційних потрясінь 1917 р., та продовжувати свою наукову і професійну діяльність за різних політичних умов. Рассмотрено личность украинского ученого, археолога и музейного деятеля Николая Биляшивского как участника важных политических процессов в Российской империи в начале ХХ в., одновременно в нескольких ипостасях: украинского патриота, кадета, думского депутата и российского земского деятеля. Освещено казус с разночтениями фамилии и отчества депутата Биляшивского. Сделана попытка проанализировать мотивы его деятельности в этот период, влияния близкого окружения на политическую позицию и принятие решений, особенности жизненной стратегии в целом. На основе архивных документов освещены конкретные обстоятельства его работы как представителя Всероссийского союза городов в занятой русскими войсками Галиции и Буковине в годы Первой мировой войны.
Отмечено, что высокий уровень специальных знаний и профессионализм Биляшивского вместе с осторожным отношением к радикальным политическим решениям позволили ему избежать репрессий от правительств, часто меняющихся в Киеве в ходе революционных потрясений 1917 г. и продолжать свою научную и профессиональную деятельность в различных политических условиях. The personality of a Ukrainian scientist, archaeologist and museum worker Bilyashivsky Mykola (1867-1926) is quite well known in the professional environment. However he can not be named a widely popular man. Soviet literature mainly covered his scientific activity. The interest in him was mainly displayed in the jubilee years. This can be explained by ambiguous political biography of the scientist. Before the 1917 revolution he was close both to the Ukrainian national movement, and the all-Russian party of constitutional democrats.
The purpose of this notice is to examine the life path near of Bilyashivsky as a partner of important political processes in the Russian Empire in the early twentieth century simultaneously in several ways: a Ukrainian patriot, a cadet, the Russian Duma deputy and a Russian Zemstvo figure.
Special attention is paid to the discrepancy with the name and surname of Bilyashivsky, launched in 1906, during the elections to the State Duma of the first convocation. Surprisingly, in Russian historiography the situation has not changed to this day. The statement that Mykola Fedotovych Bilyashivsky presented there as Mykola Fedorovych Belyashevsky that statement is incorrect.
The paper attempts to analyze the reasons for his activities during this period, the influence of close environment on his political stand and decision making and peculiarities of his live strategy in general. The role of Mychailo Hrushevsky and Fyodor Shteinhel in Bilyashivsky`s personal life and social activities is emphasized.
Based on archival documents it is highlighted the particular circumstances of his work as a representative of All-Russian Union of cities in Galicia and Bukovina occupied by Russian troops during the First World War.
It is noted that a high level of special knowledge and professionalism of Bilyashevsky and his careful attitude to radical political decisions allowed him to avoid repressions from the governments, which often changed during the shocks of 1917-1919 in Kyiv. He continued his academic and professional activities in different political conditions.
Bilyashevsky`s activities for the maintenance of Ukrainian Cultural Property in Galicia and Bukovina during the First World War and its relations with the Russian administration of the newly established General Government remains the great potential for further development.